2018
DOI: 10.1080/13825585.2018.1432746
|View full text |Cite
|
Sign up to set email alerts
|

Do attentional capacities and processing speed mediate the effect of age on executive functioning?

Abstract: The executive processes are well known to decline with age, and similar data also exists for attentional capacities and processing speed. Therefore, we investigated whether these two last nonexecutive variables would mediate the effect of age on executive functions (inhibition, shifting, updating, and dual-task coordination). We administered a large battery of executive, attentional and processing speed tasks to 104 young and 71 older people, and we performed mediation analyses with variables showing a signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 145 publications
0
4
0
Order By: Relevance
“…In that way, we observed that the effect of age encompasses the three executive processes explored, with large effect size for inhibition, while shifting and updating processes are associated to small and medium effect, respectively. A decrease in performance affecting different aspects of executive functioning simultaneously has been reported by [82]. The presence of a large age-related effect size for inhibition can seem surprising as not all inhibitory processes does seem to be impaired with aging [83].…”
Section: Aging and Executive Functionsmentioning
confidence: 91%
“…In that way, we observed that the effect of age encompasses the three executive processes explored, with large effect size for inhibition, while shifting and updating processes are associated to small and medium effect, respectively. A decrease in performance affecting different aspects of executive functioning simultaneously has been reported by [82]. The presence of a large age-related effect size for inhibition can seem surprising as not all inhibitory processes does seem to be impaired with aging [83].…”
Section: Aging and Executive Functionsmentioning
confidence: 91%
“…In that way, we observed that the effect of age encompasses the three executive processes explored, with large effect size for inhibition, while shifting and updating processes are associated to small and medium effect, respectively. A decrease in performance affecting different aspects of executive functioning simultaneously has been reported by (79). The presence of a large age-related effect size for inhibition can seem surprising as not all inhibitory processes does seem to be impaired with aging (80).…”
Section: Aging and Executive Functionsmentioning
confidence: 91%
“…Alongside the enrollment criteria, which may not have been ideal to study the impact of early life on later life and aging, the instruments, likely, were not chosen with a long-term longitudinal study in mind either. For example, processing speed has been suggested as an important mediator of changes in cognition throughout the lifespan (e.g., Salthouse, 1996;Nettelbeck and Burns, 2010;Gilsoul et al, 2019). However, the ZLS-Childhood dataset contains very limited assessments of processing speed.…”
Section: Part Of Longitudinal Datasetsmentioning
confidence: 99%